2016
DOI: 10.1111/acel.12458
|View full text |Cite
|
Sign up to set email alerts
|

Chronic senolytic treatment alleviates established vasomotor dysfunction in aged or atherosclerotic mice

Abstract: SummaryWhile reports suggest a single dose of senolytics may improve vasomotor function, the structural and functional impact of long‐term senolytic treatment is unknown. To determine whether long‐term senolytic treatment improves vasomotor function, vascular stiffness, and intimal plaque size and composition in aged or hypercholesterolemic mice with established disease. Senolytic treatment (intermittent treatment with Dasatinib + Quercetin via oral gavage) resulted in significant reductions in senescent cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
493
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 600 publications
(532 citation statements)
references
References 23 publications
11
493
1
Order By: Relevance
“…The senolytic activities and efficacies of some drugs have already been confirmed in mouse disease models (Childs et al, 2016; Farr et al, 2017; Jeon et al, 2017; Ogrodnik et al, 2017; Roos et al, 2016; Schafer et al, 2017). We used the anti‐apoptotic Bcl‐2 family inhibitor, ABT‐263, in the PPE‐induced emphysema model.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The senolytic activities and efficacies of some drugs have already been confirmed in mouse disease models (Childs et al, 2016; Farr et al, 2017; Jeon et al, 2017; Ogrodnik et al, 2017; Roos et al, 2016; Schafer et al, 2017). We used the anti‐apoptotic Bcl‐2 family inhibitor, ABT‐263, in the PPE‐induced emphysema model.…”
Section: Discussionmentioning
confidence: 94%
“…The efficacy of drugs that induce senescent cell death, namely senolytic drugs, has been demonstrated in several mouse disease models. The combination of dasatinib and quercetin, which inhibits pro‐survival kinase pathways, ameliorates cardiovascular and vasomotor functions (Roos et al, 2016; Zhu et al, 2015), hepatic steatosis (Ogrodnik et al, 2017), and IPF (Schafer et al, 2017), similar to the semi‐genetic elimination of senescent cells. The anti‐apoptotic bcl‐2 family protein inhibitors ABT‐263/737 are effective in atherosclerosis and osteoarthritis models (Childs et al, 2016; Jeon et al, 2017) and improve stem cell functions and other aging‐associated phenotypes (Chang et al, 2016; Yosef et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Senescent cells have been demonstrated to disrupt tissue structure and function through the secretion of pro‐inflammatory cytokines, chemokines, and proteases, a feature termed the senescence‐associated secretory phenotype (Campisi & d'Adda, 2007; Vicente, Mausset‐Bonnefont, Jorgensen, Louis‐Plence, & Brondello, 2016). Recent studies have demonstrated that selectively eliminating senescent cells can attenuate several age‐dependent disorders (Baker et al., 2011; Chang et al., 2016; Roos et al., 2016; Zhu et al., 2015). The relationship between autophagy and senescence is still subject to debate (Kang & Elledge, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was demonstrated that chronic clearance of p16INK4a-positive cells in adult mice extends the median lifespan of naturally aged mice (27). Clearance of senescent cells in versions of this genetic model (INK-ATTAC and 3MR mice) or treating mice with novel senolytics extended healthspan (31,32), restored vascular reactivity (33), stabilized atherosclerotic plaques (34), improved pulmonary function (35), alleviated osteoarthritis (28), improved fatty liver disease (36) and improved lung function in a pulmonary fibrosis model (35). Conversely, injecting senescent cells is able to drive agerelated diseases such as osteoarthritis (37).…”
Section: Cellular Senescencementioning
confidence: 99%